Kesetaraan Gender Mendorong Wanita Sebagai Pemimpin Yang Berpengaruh Dan Berdaya Saing - M. Yogi Riyantama Isjoni; Muhammad Ikhsan; Adinda Asmaratul Husni; Deska Nindia Putri; Diah Uli Tua; Fitriani Tricahyani; Grisdienta Carriffino; Lusiana Wulandari; Nasya Travika; Nildatul Husna; Wiranto Wajiha Wudda (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Gender equality is an important human rights principle to be realized in Indonesia. Although there has been significant progress in achieving gender equality, major challenges remain, especially in overcoming discrimination against women. One solution to achieving gender equality is to encourage women to become influential and competitive leaders. This research describes the method of implementing gender equality socialization, its results and achievements, as well as the importance of women in leadership. This effort involves outreach targets such as women's groups, teenagers and the general public through materials that emphasize that women also have rights in various fields, including politics and economics. In this socialization process, the presenters who are legislative candidates become resource persons to provide inspiration to the participants. Evaluation is carried out to measure participants' understanding of the socialization material. The results show that women have great potential as influential leaders if given equal opportunities and support.